The divergence-convergence model of acquired neuroprotection - Bas Orth, Carlos; Bading, Hilmar (Mechanisms of development, 2013)
It is commonly known that mental activity helps to maintain a healthy brain. Recent research has unraveled the underlying molecular mechanisms that explain why an active brain lives longer. These mechanisms involve the activation of a comprehensive transcriptional program that is triggered by enhanced synaptic activity and renders neurons resistant to harmful conditions. Functionally, this state of acquired neuroprotection may be achieved mainly via one mechanism, which is the stabilization of mitochondria. In this review we propose a model that describes the signaling network that links synaptic activity to neuroprotection. We suggest that the divergent-convergent architecture of this signaling network ensures both robust and reliable as well as persistent activation of the neuroprotective machinery.
Published online: 10 October 2012
Gesehen am 04.05.2018